Annual Research Review: Digital health interventions for children and young people with mental health problems – a systematic and meta‐review. (10th December 2016) - Hollis, Chris; Falconer, Caroline J.; Martin, Jennifer L.; Whittington, Craig; Stockton, Sarah; Glazebrook, Cris; Davies, E. Bethan
Abstract : Background: Digital health interventions (DHIs), including computer‐assisted therapy, smartphone apps and wearable technologies, are heralded as having enormous potential to improve uptake and accessibility, efficiency, clinical effectiveness and personalisation of mental health interventions. It is generally assumed that DHIs will be preferred by children and young people (CYP) given their ubiquitous digital activity. However, it remains uncertain whether: DHIs for CYP are clinically and cost‐effective, CYP prefer DHIs to traditional services, DHIs widen access and how they should be evaluated and adopted by mental health services. This review evaluates the evidence‐base for DHIs and considers the key research questions and approaches to evaluation and implementation. Methods: We conducted a meta‐review of scoping, narrative, systematic or meta‐analytical reviews investigating the effectiveness of DHIs for mental health problems in CYP. We also updated a systematic review of randomised controlled trials (RCTs) of DHIs for CYP published in the last 3 years. Results: Twenty‐one reviews were included in the meta‐review. The findings provide some support for the clinical benefit of DHIs, particularly computerised cognitive behavioural therapy (cCBT), for depression and anxiety in adolescents and young adults. The systematic review identified 30 new RCTs evaluating DHIs for attention deficit/hyperactivity disorder (ADHD), autism, anxiety, depression, psychosis, eating disorders and PTSD. The benefits of DHIs in managing ADHD, autism, psychosis and eating disorders are uncertain, and evidence is lacking regarding the cost‐effectiveness of DHIs. Conclusions: Key methodological limitations make it difficult to draw definitive conclusions from existing clinical trials of DHIs. Issues include variable uptake and engagement with DHIs, lack of an agreed typology/taxonomy for DHIs, small sample sizes, lack of blinded outcome assessment, combining different comparators, short‐term follow‐up and poor specification of the level of human support. Research and practice recommendations are presented that address the key research questions and methodological issues for the evaluation and clinical implementation of DHIs for CYP. Abstract : Read the Commentary on this article at doi:10.1111/jcpp.12715